Struktur Formula Petualangan dan Nilai Pendidikan Karakter dalam Dongeng Pohon Impian Karya Watiek Ideo - Ulhaq, Salma Dhiya (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One of the reasons why John G. Cawelti's formula appears is because many popular literary stories have the same formula. This study aims to describe and analyze the structure of Cawelti's adventure formula that builds the fairy tale of the Dream Tree story and classifies the character education values contained in the fairy tale of the Dream Tree by Watiek Ideo. The research analysis used descriptive qualitative, read carefully and recorded the reading data from the fairy tale The Dream Tree by Watiek Ideo as the object of research. The data that has been found is then analyzed and classified based on each group. The results of this study can be seen that the fairy tale The Dream Tree fulfills the three elements of Cawelti's adventure formula. It is known that the fairy tale formula is similar to The Lord Of The Rings. The adventure plot formula is: (1) The events behind the hero's journey; (2) the journey undertaken by the hero through the many obstacles faced in completing the mission; (3) the hero encounters a hero on the way; (4) hero successfully completes the journey, and faces the antagonist; (5) hero has a new problem; (6) the hero's victory for his efforts in completing the mission. Meanwhile, the values of character education contained in the fairy tales of the Dream Tree, include strong determination, loving and respecting parents, fighting fear, and cooperation.